CLINICAL AND SOCIAL CHARACTERISTICS OF PENAL INSTITUTIONS INMATES WITH NEWLY DIAGNOSED PULMONARY TUBERCULOSIS - N. M. Koretskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The spread of tuberculosis in the penitentiary system institutions has a significant impact on the epidemic situation in the country. The aim of the research is to study the clinical and social characteristics of newly diagnosed patients with pulmonary tuberculosis among the special contingent prisons. Analyzed data include 107 cases of pulmonary tuberculosis newly diagnosed in 2014 among inmates of penitentiary institutions. We studied the age structure of the patients, their educational level, number of previous convictions, family status, addictions and comorbidity, ways of revealing pulmonary tuberculosis, the structure of its clinical forms and characteristics of the specific process. It is established that in the conditions of penitentiary system tuberculosis often affects repeatedly convicted persons with low education level; and in most cases, the disease develops in the first two years of imprisonment. Low level of health literacy of patients, along with the lack of family in more than 2/3 of cases, reduces the motivation and commitment to treatment. We concluded that there is a need for sanitary-educational work of two directions among persons in penal institutions. First, healthy individuals should be filled in on clinical symptoms of pulmonary tuberculosis and with a focus on the need to seek medical help immediately after its occurrence. Second, to reduce the refused treatment rate, the continuous and purposeful work must be done to form commitment to therapy.